CFD SIMULATION OF NATURAL CONVECTION HEAT TRANSFER IN NANOFLUIDS - KE XIN, LOKE (IRC, 2017)
Nanofluids are classified as promising heat transfer medium due to their remarkable heat transfer enhancement properties. A significant amount of studies in this field has been carried out extensively to analyze the usage of nanofluids in the improvement of thermal management. However, limited studies are reported in terms of numerical investigation, especially on the effect of thermophysical properties in nanofluids’ heat transfer behavior in an enclosure. Hence, this project is carried out to numerically investigate the heat transfer characteristic of alumina-oil nanofluids in a 3-dimentional rectangular enclosure in terms of the effect of temperature range (20K ≤ ΔT ≤ 60 K), nanoparticles concentration (0 ≤ wt% ≤ 3.0) and thermophysical properties (density, viscosity, thermal conductivity and specific heat capacity), using Computational Fluid Dynamics (CFD) simulation tool ANSYS Fluent 15.0. The overall heat transfer performance was analyzed computationally in terms of Nusselt number, Rayleigh number and overall heat transfer coefficient, as well as the velocity and temperature distribution in the enclosure. Significant increase in heat transfer coefficient can be observed with increasing of nanoparticles, whereby the optimum temperature difference between hot and cold surface lies on 40K. Each thermophysical property of nanofluid carries significant effect on heat transfer performance. Density and thermal conductivity exert beneficial effects whereas viscosity and heat capacity deteriorate heat transfer performance of nanofluid.